USE OF THE WORD ‘ANAK’ (CHILD) IN INDONESIAN FROM ECOLINGUISTIC PERSPECTIVE - Praptomo Baryadi Isodarus (Sanata Dharma University, 2022)
This article presents the results of research on the use of the word ‘anak’ (child) in Indonesian compound words from an ecolinguistic perspective. The problem studied is whether the use of the word ‘anak’ in Indonesian compound words has a relationship with the environment. When it shows a relationship with the environment, what type of environment will the word ‘anak’ in Indonesian compound words refer to? Because the problem is studied from an ecolinguistic perspective, the theory used in this research is the theory of language in relation to the environment. Language whose manifestation is in the form of grammatical units is assumed to designate a certain type of environment as its reference. The data of this research are in the form of compound words which contain the word ‘anak’ in Indonesian. The data were taken from a primary source, namely the online version of the Kamus Besar Bahasa Indonesia (2015), and from a secondary source, namely the researcher's introspective data as a native Indonesian speaker. The data were collected by the referential method and analyzed by the referential equivalent method. The results of data analysis were presented with informal methods and formal methods. The results of this study indicate that the use of the word ‘anak’ in Indonesian compound words refers to ten types of environment, namely (1) the family environment, (2) the educational environment, (3) the work environment, (4) the place environment, (5) the socio-economic environment, (6) the socio-ethical environment, (7) the animal environment, (8) the plant environment, (9) the natural environment, and (10) the artificial object environment. This finding is one of the evidences that language has a relationship with the environment.